KRYTYCZNE WYBORY USTROJOWE W POKOMUNISTYCZNEJ TRANSFORMACJI - Kamiński, Antoni Z. (Wydział Prawa i Administracji UAM, 2007)
The article seeks to identify internal factors explaining the diversity in evolutionary paths of post-communist countries. We build our analytical framework around three actors (Communist Establishment, Society and Opposition) and use the status in their patterns of mutual relations to explain fundamental choices in transition from central planning and totalitarian political regime. These choices involve strategy of economic transformation, the type of government, and the electoral system. Three cases emerge from this analysis: (1) Communist Establishment in control; (2) co-habitation between the Opposition and the Communist Establishment; (3) the Opposition in charge. Each o f these cases implies a different evolutionary path driven by strategic choices made and thereby different outcomes. Case (3) has generated the path with lower economic adjustment costs and producing democracy. In contrast, the case (1) has tended to produce regimes with limited political and economic freedoms.